Physical activity in people with axial spondyloarthritis and the impact of overall attitudes, barriers, and facilitators: A cross‐sectional study. (19th July 2020) - Rasmussen, Jens Ole; Primdahl, Jette; Fick, Willy; Bremander, Ann
Abstract: Objective: To study the association between self‐reported physical activity level and overall attitudes and barriers to and facilitators of physical activity in people with axial spondyloarthritis (axSpA), and to compare health status and quality of life (QoL) in people with different levels of physical activity. Methods: Four hundred forty‐five members of the Danish Patient Association for Axial Spondyloarthritis completed an online survey including questions on physical activity, overall attitudes, barriers, and facilitators to physical activity, health, and QoL. Nonparametric tests and logistic regression analyses were performed. Results: The response rate was 46%, median age 56 years (range 22–85), and 54% were men. In all, 23% reported low physical activity (physical activity ≥30 min on a moderate intensity level ≤1 day/week), 36% were moderately physically active (2–3 days/week), and 41% reported high physical activity (≥4 days/week). In a multivariate model, high physical activity was associated with a positive overall attitude ("physical activity is ok, " OR 5.44, 95%CI [1.24, 23.87], and "I like physical activity, " OR 14.22, 95%CI [3.34, 60.61]), and higher disagreement with barriers to physical activity, OR 1.12, 95%CI [1.07, 1.17]). People with moderate or high physical activity levels reported better self‐perceived health and QoL, compared with those with low physical activity level ( p ≤ 0.003). Conclusion: To support changes in physical activity level in people with axSpA, health professionals need to discuss attitudes and barriers to physical activity with their clients. Barriers seem to be of greater significance than facilitators of any kind.